Role of Stromal Myofibroblasts in the Progression of Oral Lesions from Dysplasia to Invasive Carcinoma - Khalid, Aeman; Siddiqui, Safia; Faizi, Nafis; Hassan, Jowairiah; Nehal, Naila; Siddiqui, Atiuddin (Indian Journal of Medical and Paediatric Oncology, 2019)
Background: Concurrent with the conversion of nondiseased epithelial tissue to precancerous epithelium and finally to carcinoma, the stroma also changes from normal-to-primed to tumor-associated reactive stroma. Cancerous cells secrete cytokines that promote differentiation of fibroblasts into cancer-associated fibroblasts/myofibroblasts. Myofibroblasts are tumor promoting and correlate with poor survival in many cancers. Vimentin expression is noted in epithelial cells of histologically more malignant oral squamous cell carcinoma (OSCC). Aim and Objectives: The aim of this study is to understand the role of tumor microenvironment by analyzing the expression of α-smooth muscle actin (α-SMA) in stromal myofibroblasts and to find a possible association between intensity and pattern of myofibroblast expression and progression of oral lesions from mild, moderate, and severe dysplasia to verrucous and invasive carcinomas. Materials and Methods: The study was divided into two groups. Sixty cases of premalignant lesions and 60 cases of OSCC were taken as the study groups. Smooth muscle cells surrounding the blood vessels were taken as positive control (internal control). Immunohistochemistry (IHC) for α-SMA was performed for the identification of myofibroblasts. The cases were then assessed for intensity and pattern of myofibroblastic proliferation. IHC for vimentin-positive epithelial cells was also done. Results: Fisher’s exact test and Chi-square test were used. There was an increased α-SMA expression in malignant cases. Few cases of dysplasia showed focal staining pattern, whereas network pattern predominated in invasive carcinomas. Vimentin expression was seen in histologically more malignant OSCC cases and higher number of myofibroblasts was observed in such cases. Conclusion: Myofibroblasts increase as the disease progresses. Network arrangement of myofibroblasts represents higher invasive characteristics and a weaker prognosis.
Keywords: Alpha-smooth muscle actin; cancer-associated fibroblasts; dysplasia; myofibroblast; oral squamous cell carcinoma